Consumer Preferences in Purchase Decisions Based on Price and Product Quality of SayStory in Surakarta - Safira Nur Annisa; Marfuatush Sholihah, Putri; Firdausy, Daris Nabil; Hanif Alfikri, Muhammad; Rahmadhini, Marjam Desma (LP2M IBK Nitro, 2025)
This research aims to analyze consumer preferences in purchasing decisions of Say Story products in Surakarta based on price and product quality factors. The background of this research is based on the importance of understanding how price and product quality influence consumer purchasing decisions, especially in the context of beverage products such as Say Story. The research method used is quantitative descriptive with data collection through questionnaires distributed to Say Story consumers in Surakarta. Data were analyzed using chi square analysis techniques to test the effect of price and product quality on purchasing decisions. The results of the research indicate that both price and product quality have a significant influence on purchasing decisions, with product quality being a more dominant factor. These findings provide practical implications for Say Story business owners in designing effective marketing strategies, especially in balancing price and quality to meet consumer preferences.